Diagnostic Anatomy of the Maxillofacial Region on Orthopantomograph - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
The purpose of the present article was to review the physics and radiation factor of the orthopantomograph and to describe the diagnostic anatomy visualised on the imaging modality. Literature search was done via PubMed, EMBASE, Cochrane electronic databases and Google Scholar. The keywords for the search were orthopantomograph, anatomy, maxillofacial region and physics. The search was restricted to articles written in English Language and published within the years 1940–2016. The search was further limited to review, free full-text articles. The available literature was reviewed, and the physics and radiation exposure of patients undergoing orthopantomograph imaging were discussed. The radiation exposure was compared to the complete mouth series intra-oral periapical radiographs. Furthermore, the diagnostic anatomy of the maxillofacial region, as visualised on the orthopantomograph, was reviewed. The clinical relevance of the various anatomic structures was also discussed. The knowledge of maxillofacial anatomy on the orthopantomograph can be challenging due to distortion and superimposition of anatomic structures. However, a good understanding of the normal enables the clinician to identify the abnormal.